Development of MOOC content with STEM approach and its influence on students’ geographical literacy - Purwanto Purwanto; Felix Andika Dwiyanto; Wako Uriu (Universitas Negeri Malang, 2024)
This research aims to develop MOOC content with a STEM approach using the Schoology Learning Management System (LMS) and apply the developed product to assess its impact on students' geographical literacy abilities. The research falls under the category of Research and Development (R&D) with a mixed-method analysis. The development model used in this study is ASSURE. The research design implemented the one-group pretest-posttest design with the N-gain score test when a significant difference was found between the average pretest and posttest scores through the paired sample T-Test. The N-gain score was then used to determine the product’s effectiveness based on Heke’s category. Then, the trial subjects were selected by purposive sampling method based on the location and school criteria. The data collection instruments used were interviews and questionnaires. The study's findings show that the MOOC content developed using a STEM approach on the LMS Schoology is highly commendable, with a score of 98.8 percent. Furthermore, the analysis indicates a significant improvement in students' geographical literacy skills, as demonstrated by the N-gain test results, which show a high gain score of 0.7105. These outcomes confirm that using the STEM approach in MOOC content within the LMS Schoology is effective in enhancing students' geographical literacy.